Economic impacts of technology, population growth and soil erosion at watershed level: The case of the Ginchi in Ethiopia - Okumu, B.N.; Russell, N.; Jabbar, M.A.; Colman, D.; Mohamed Saleem, M.A.; Pender, J.L. (Wiley, 2004)
A dynamic bio-economic model is used to show that, without technological and policy intervention, soil loss levels, income and nutrition could not be substantially or sustainably improved in a highland area of Ethiopia. Although cash incomes could rise by more than 40% over a twelve-year planning period, average per ha soil losses could be as high as 31 tonnes per ha. With the adoption of an integrated package of new technologies, however, results show the possibility of an average two-and-a-half-fold increase in cash incomes and a 28% decline in aggregate erosion levels even with a population growth rate of 2.3%. Moreover, a minimum daily calorie intake of 2000 per adult equivalent could be met from on-farm production with no significant increases in erosion. However, higher rates of growth in nutritional requirements and population introduce significant strains on the watershed system. From a policy perspective, there is a need for a more secure land tenure policy than currently prevailing to facilitate uptake of the new technology package, and a shift from the current livestock management strategy to one that encourages livestock keeping as a commercial enterprise. It would also imply a shift to a more site-specific approach to land management.